PERAN MAHKAMAH KONSTITUSI TERKAIT PERLINDUNGAN HAK PILIH WARGA NEGARA INDONESIA DALAM PEMILU 2019 MELALUI PUTUSAN MK NOMOR 20/PUU-XVII/2019 - Pradina, Gita; Husodo, Jadmiko Anom (Res Publica: Jurnal Hukum Kebijakan Publik, 2020)
Judging from Indonesia’s current democratic process, it has aroused reactions from the community in this case Indonesian citizens who are the subject of democracy because sovereignty is in the hands of the people. The implementation of people’s sovereignty is then outlined in the General Election process which is also regulated in Law Number 7 of 2017. Then discussed the problem of simultaneous GeneralElection which was first held in 2019 Law Number 7 of 2017 concerning Elections which can be elected, Reducing , and Eliminating the Right to Vote. Through Decision of the Constitutional Court Number 20/PUU-XVII/2019, the Constitutional Court gave a decision determining its role as an institution authorized by the 1945 Constitution of the Republic of Indonesia and Law Number 8 of 2011 concerning Amendments to Law Number 24 of 2003 about the Constitutional Court.